Motor expressions: towards a redirection of the disciplinary field of physical education in a colombian public university (Impetus, 2026)
This article examines how motor expressions are understood, valued, and taught within a Bachelor’s program in Physical Education and Sport of the Universidad de los Llanos, focusing on conceptual appropriation, social relevance, and processes of learning and unlearning. Using a qualitative design, we collected data through in-depth interviews and focus groups. Analysis centered on the two constitutive dimensions of motor expressions—body and motricity—and on the program’s recent curricular readjustment from an experiential perspective. Findings indicate that adoption of motor expressions is advancing at both individual and collective levels. We conclude that foregrounding motor expressions opens alternative ways of conceptualizing body and motricity, supports efforts to counter exclusion and social inequality, and expands the scope of teaching, learning, and professional formation in physical education.
Keywords: Curriculum development; Embodied learning; Physical education; Psychomotor skills; Qualitative research; Social inclusion; Movement education